A high-density fine-grained doped tungsten-based material and preparation method thereof

Through two sintering processes of medium frequency sintering first and isostatic pressure after heat, the problem of doped tungsten-based materials in the prior art is solved, and the coordinated development of high-density and fine grains is achieved is achieved, and the density and strength of the material are significantly improved.

CN119220845BActive Publication Date: 2025-03-14CMT RARE METAL ADVANCED MATERIALS (HUNAN) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411761361.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-14
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

It is difficult to obtain high-density and fine grain doped tungsten-based materials at the same time in the prior art, and the medium frequency sintering and thermal isostatic pressing techniques have shortcomings in controlling grain size.

Method used

Two sintering processes are adopted with medium frequency sintering first and isostatic pressure after heat. By precisely controlling the heating process and insulation time, combined with hydrogen flow to eliminate impurities and seal the pores, the high density of the material and the formation of fine grains are achieved.

Benefits of technology

A high-density fine-grained tungsten-based material with high density and small particle size was prepared. The measured density was 19.0~19.2g/cm3, the relative density was ≥99%, and the average grain intercept was 2~4μm, which significantly improved the density and strength of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220845B_ABST
    Figure CN119220845B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-density fine-grained doped tungsten-based material and a preparation method thereof, which relates to the technical field of doped tungsten-based materials, and comprises the following steps: S1. wet-grinding and drying tungsten powder and metal compound powder to obtain doped tungsten powder material; S2. pressing the doped tungsten powder material into a compact; S3. subjecting the compact to medium frequency sintering and hot isostatic pressing to obtain a high-density fine-grained doped tungsten-based material. The high-density fine-grained doped tungsten-based material prepared by the present invention is subjected to a two-sintering process of "medium frequency sintering first, then hot isostatic pressing", and the two-sintering processes are strictly controlled, so that the obtained high-density fine-grained doped tungsten-based material has high density and small particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of doped tungsten-based materials, and in particular relates to a high-density fine-grain doped tungsten-based material and a preparation method thereof. Background Art

[0002] The density (relative density) and grain size of doped tungsten-based materials are two key physical indicators that affect material performance. There is a contradiction between requiring high density and grain size at the same time. In terms of the corresponding process, in order to obtain high density, it is necessary to increase the sintering temperature and extend the sintering time; and in order to obtain fine grains, it is necessary to reduce the sintering temperature and shorten the sintering time. Therefore, it is difficult to obtain industrial manufacturing of doped tungsten-based materials with high density and small grain size.

[0003] At present, the patent document with application number CN201911034977.4 proposes a sintering method for high-density rare earth tungsten electrodes, which adopts a secondary sintering technology of medium frequency sintering combined with hot isostatic pressing. However, the medium frequency sintering and hot isostatic pressing used in this patent are carried out according to the conventional temperature of sintering tungsten-based materials. The product particle size obtained by medium frequency sintering is coarse grains of 10~100μm, and after high-temperature hot isostatic pressing treatment, the grain size may be further increased to 100μm level. Such a process does not give full play to the advantages of hot isostatic pressing in controlling the grain size of tungsten-based products, but rather regards it more as a pressure processing process; in addition, the coarse-grained tungsten products produced by this patent and the fine-grained tungsten-based products in the scheme of the present invention have significant differences in application fields. Summary of the invention

[0004] In order to solve the above technical problems, a high-density fine-grained doped tungsten-based material and a preparation method thereof are provided. The preparation method of the present invention adopts a two-sintering process of "medium frequency sintering first and then hot isostatic pressing", and the two sintering processes are strictly controlled. The obtained high-density fine-grained doped tungsten-based material has high density and small particle size.

[0005] The present invention solves the above technical problems through the following technical solutions.

[0006] The present invention discloses a method for preparing a high-density fine-grained doped tungsten-based material, comprising the following steps:

[0007] S1. Wet-grinding and drying the tungsten powder and the metal compound powder to obtain a doped tungsten powder;

[0008] The metal compound is an oxide of a IIIB~VB group element or a carbide of a IIIB~VB group element; wherein IIIB~VB refers to group IIIB, group IVB, and group VB;

[0009] S2. The tungsten-doped powder is pressed into a compact to obtain a green compact;

[0010] S3. The compact is subjected to medium frequency sintering and hot isostatic pressing to obtain a high-density fine-grained doped tungsten-based material;

[0011] The medium frequency sintering is divided into a heating process and a high temperature sintering process; the heating process includes four insulation platforms: the temperature of the first insulation platform is 800-1000°C, the temperature of the second insulation platform is 1050-1250°C, the temperature of the third insulation platform is 1350-1550°C, and the temperature of the fourth insulation platform is 1600-1800°C; the set temperature of the high temperature sintering is 1900-2100°C;

[0012] The set temperature of the hot isostatic pressing is 1650~1850℃.

[0013] In S1, the tungsten powder is conventional tungsten powder in the art.

[0014] Further in S1, the particle size of the tungsten powder is 0.5-1.0 μm.

[0015] Further in S1, the purity of the tungsten powder is ≥99.9%.

[0016] In S1, the particle size of the metal compound powder is 0.01-1.0 μm, for example, 0.1 μm.

[0017] Further in S1, the oxide of the IIIB~VB group element is La 2 O 3 、CeO 2 、Sm 2 O 3 , Y 2 O 3 and Nd 2 O 3 One of;

[0018] Further in S1, the carbide of the IIIB~VB group element is one of ZrC, HfC and TiC.

[0019] In S1, the metal compound is La 2 O 3 、CeO 2 、Sm 2 O 3 , Y 2 O 3 、Nd 2 O 3 , ZrC, HfC and TiC.

[0020] In S1, the content of metal compound in the doped tungsten powder material is 0.5-2.0 wt %, and the remainder is tungsten powder.

[0021] In S1, the inner lining of the wet grinding tank is a hard alloy plate, and the outer shell of the tank is a steel shell.

[0022] In S1, the wet grinding medium is anhydrous ethanol, and the volume mass ratio of the anhydrous ethanol to the doped tungsten powder is 100-300 mL / kg; wherein, the amount of alcohol used can be reduced as the particle size of the tungsten powder becomes coarser.

[0023] In S1, the mass ratio of the wet-milled ball to the material is 2:1 to 8:1; preferably, the mass ratio of the wet-milled ball to the material is 4:1. The ball is a cemented carbide ball.

[0024] In S1, the rotation speed of the wet grinding is 30-300 rpm, for example, 60 rpm.

[0025] In S1, the wet grinding time is 10-16 hours, for example 12 hours.

[0026] In S1, the wet grinding is followed by drying and sieving.

[0027] In S1, the drying process is a conventional operation in the art; the drying is carried out in a vacuum oven.

[0028] In S1, the drying temperature is 50-90°C, preferably 60-80°C, for example 70°C.

[0029] In S1, the drying time is 12 to 24 hours, for example, 16 hours; the drying is performed until constant weight.

[0030] In S1, after drying, the material needs to be sieved through a 120-mesh sieve twice.

[0031] In S2, the pressing method is cold isostatic pressing, and the process of cold isostatic pressing is a conventional process in the art.

[0032] In S2, the pressing pressure is 160-240 MPa, preferably 180-220 MPa, for example 200 MPa.

[0033] In S2, the holding time of the pressing is 5 to 10 minutes.

[0034] In S2, the pressing adopts a rubber soft mold and an outer steel mold, the rubber soft mold is used to contain the doped tungsten powder material, and the steel mold plays a shaping role outside the soft mold.

[0035] In S3, the medium frequency sintering is divided into a heating process and a high temperature sintering process.

[0036] In S3, the heating rate of the medium frequency sintering is 2-30°C / min, preferably 5-15°C / min.

[0037] Further in S3, the temperature rising process includes four insulation platforms, and the insulation time at each insulation platform is independently selected from 1 to 4 hours.

[0038] Further in S3, the heating process includes four heat preservation platforms:

[0039] The temperature of the first insulation platform is 800~1000℃, and it is kept at this temperature for 1~4h;

[0040] The temperature of the second insulation platform is 1050~1250℃, and it is kept at this temperature for 1~4h;

[0041] The temperature of the third insulation platform is 1350~1550℃, and it is kept at this temperature for 1~4h;

[0042] The temperature of the fourth insulation platform is 1600~1800℃, and it is kept at this temperature for 1~4h.

[0043] Further in S3, for example, the heating process includes four heat preservation platforms:

[0044] The temperature of the first insulation platform is 900°C and is maintained at this temperature for 2 hours;

[0045] The temperature of the second insulation platform is 1150°C, and it is kept at this temperature for 3-4 hours;

[0046] The temperature of the third insulation platform is 1450℃, and it is kept at this temperature for 3~4h;

[0047] The temperature of the fourth insulation platform is 1700℃, and it is kept at this temperature for 2h. Among them, during the process of the first insulation platform and the second insulation platform, the reaction of oxygen and hydrogen significantly reduces the oxygen content and effectively discharges the impurity gas in the compact. During the process of the third insulation platform and the fourth insulation platform, impurities with low melting points can be excluded, which not only helps to reduce the impurity content of the product, but also helps to form a dense crystal structure and uniform grain distribution. These processes can effectively improve the density, strength and microstructure of the material.

[0048] In S3, the heating process needs to maintain hydrogen flow, and the hydrogen flow rate is 5-20 m 3 / h. Hydrogen, as a protective gas, can isolate the air and protect tungsten from oxidation. It can also significantly reduce the oxygen content in the powder by reacting with oxygen to produce water. The circulating hydrogen can promptly take away the generated water vapor, as well as various gas elements and low-melting-point impurities volatilized from the blank.

[0049] Further in S3, the setting temperature of the high temperature sintering is 1900-2100°C, and the temperature is kept at the setting temperature for 0.5-2h, preferably 0.5-1.5h after reaching the setting temperature of the high temperature sintering. The high temperature sintering can achieve the crystallization of fine particles in the green compact and close the pores on the surface of the green compact.

[0050] In S3, the introduction of hydrogen is stopped when the medium frequency sintering reaches 1800-2000° C. For example, the introduction of hydrogen is stopped when the medium frequency sintering reaches 1800° C. No further introduction of hydrogen is required during the high temperature sintering process, and the hydrogen atmosphere can be maintained.

[0051] In S3, after the medium frequency sintering, the furnace needs to be cooled to 20-30°C, preferably 20-25°C.

[0052] In S3, the setting temperature of the hot isostatic pressing is 1650-1850°C, preferably 1700-1800°C.

[0053] Further in S3, after the hot isostatic pressing is heated to the set temperature, it is kept at this temperature for 2.0 to 4.0 hours.

[0054] In S3, the pressure of the hot isostatic pressing is 100-200 MPa.

[0055] In the present invention, hot isostatic pressing can ensure that the secondary densification of the material is achieved without causing the grains to grow too thick.

[0056] The present invention also discloses a high-density fine-grain doped tungsten-based material prepared by the above-mentioned preparation method of the high-density fine-grain doped tungsten-based material.

[0057] The measured density of the high-density fine-grained tungsten-based material is 19.0-19.2 g / cm 3 Preferably, the measured density of the high-density fine-grained tungsten-based material is 19.01-19.11 g / cm 3 .

[0058] The relative density of the high-density fine-grained doped tungsten-based material is ≥99%; preferably, the relative density of the high-density fine-grained doped tungsten-based material is 99.1-99.4%; more preferably, the relative density of the high-density fine-grained doped tungsten-based material is 99.14-99.33%;

[0059] Among them, the relative density of high-density fine-grained doped tungsten-based materials = measured density / theoretical density × 100%.

[0060] The grain density of the high-density fine-grained tungsten-based material is 60,000 to 200,000 grains / mm 2 , the best is 80,000~180,000 / mm 2 .

[0061] The average intercept of the grains of the high-density fine-grained doped tungsten-based material is 2-4 μm, preferably 2.0-3.1 μm, wherein the average intercept can represent the average grain size.

[0062] As mentioned above, the high-density fine-grained doped tungsten-based materials are used in the fields of high-temperature resistant, high-strength or high-toughness materials; preferably, they are used in aerospace, rare earth smelting, and nuclear fields; for example, they are used in the first wall material of the Tokamak device of a nuclear fusion reactor.

[0063] In contrast, the fine-grained tungsten-based products studied in this patent application are mainly targeted as the first wall material of the Tokamak device of a controlled nuclear fusion reactor. This application field requires the use of tungsten-based materials with very fine grains. The smaller the grains, the greater the strength and hardness of the material, because small grains increase the dislocation density of the material, thereby enhancing the mechanical properties of the material. Small grains can also improve the ductility and toughness of the material, because small grains can reduce the chance of crack propagation. In addition, small grains have better corrosion resistance and ablation resistance. Therefore, in the fields of aviation, aerospace, nuclear power, etc., high-temperature resistant, high-strength, and high-toughness materials are required, and small-grained tungsten-based materials are a good choice. This is completely different from the electrode material mentioned in patent CN110788318A. Therefore, although both involve the sintering technology of tungsten-based materials, their process requirements and application targets are essentially different.

[0064] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] 1. The present invention achieves multiple technical advantages by precisely controlling the temperature rise process of medium frequency sintering. First, it can effectively remove impurities, which is crucial for the purity of the material. Second, this process helps to form a high-density fine-grained doped tungsten-based material with dense and uniformly distributed grains. Finally, through high-temperature sintering, the pores on the surface of the green compact can be closed, further improving the density and strength of the material.

[0067] 2. The hot isostatic pressing sintering technology used in the present invention is carried out at a relatively low temperature, which not only achieves high densification of the material, but also avoids a series of problems in the traditional hot isostatic pressing process, such as the need to use a sheath, the stringent requirements on the sheath material of the tungsten product, and the low yield problem when the sheath is stripped. Therefore, the high-density fine-grained doped tungsten-based material prepared by the present invention has the characteristics of high yield.

[0068] 3. The high-density fine-grained doped tungsten-based material prepared by the present invention has a measured density of 19.0-19.2 g / cm 3, relative density ≥ 99%, showing extremely high density. The grain density is between 60,000 and 200,000 / mm², and the average grain intercept is 2-4μm. Therefore, the high-density fine-grained doped tungsten-based material of the present invention has both high-density and fine-grained properties, indicating that the material has excellent microstructure and performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 This is the metallographic and grain data diagram of the high-density fine-grained doped tungsten-based material of Example 1.

[0070] Figure 2 This is a scanning electron microscope image of the cross-section of the high-density fine-grained doped tungsten-based material of Example 1.

[0071] Figure 3 This is the energy spectrum of the high-density fine-grained tungsten-based material doped in Example 1.

[0072] Figure 4 This is the metallographic and grain data diagram of the high-density fine-grained doped tungsten-based material of Example 2.

[0073] Figure 5 This is a scanning electron microscope image of the cross-section of the high-density fine-grained doped tungsten-based material of Example 2.

[0074] Figure 6 This is the metallographic and grain data diagram of the high-density fine-grained doped tungsten-based material of Example 3.

[0075] Figure 7 This is a scanning electron microscope image of the cross-section of the high-density fine-grained doped tungsten-based material of Example 3.

[0076] Figure 8 This is the energy spectrum of the high-density fine-grained tungsten-based material doped in Example 3.

[0077] Fig. 9 This is the metallographic and grain data diagram of the high-density fine-grained doped tungsten-based material of Example 4.

[0078] Fig.10 This is a scanning electron microscope image of the cross-section of the high-density fine-grained doped tungsten-based material of Example 4.

[0079] Fig.11 This is the energy spectrum of the high-density fine-grained tungsten-based material doped in Example 4.

[0080] Fig.12 This is the metallographic and grain data diagram of the high-density fine-grained doped tungsten-based material of Example 5.

[0081] Fig.13 This is a scanning electron microscope image of the cross-section of the high-density fine-grained doped tungsten-based material of Example 5.

[0082] Fig.14 This is the energy spectrum of the high-density fine-grain doped tungsten-based material of Example 5.

[0083] Fig.15 This is the metallographic and grain data diagram of the high-density fine-grained doped tungsten-based material of Example 6.

[0084] Fig.16 This is a scanning electron microscope image of the cross-section of the high-density fine-grained doped tungsten-based material of Example 6.

[0085] Fig.17 This is the energy spectrum of the high-density fine-grained tungsten-based material doped in Example 6.

[0086] Fig.18 This is the metallographic and grain data diagram of the doped tungsten-based material of Comparative Example 1.

[0087] Fig.19 This is an electron microscope image of the cross-section of the product after medium-frequency sintering of the doped tungsten-based material of Comparative Example 1.

[0088] Fig. 20 This is the metallographic and grain data diagram of the doped tungsten-based material of Comparative Example 2.

[0089] Fig.21 This is a scanning electron microscope image of the cross-section of the doped tungsten-based material of Comparative Example 2. DETAILED DESCRIPTION

[0090] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.

[0091] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0092] The tungsten powder in the following examples is 06 type pure tungsten powder with an average particle size of 0.6 μm and a purity of 99.95%.

[0093] For the sintering of tungsten-based materials, the hot isostatic pressing process can cause serious defects in the product:

[0094] First, the blank needs to be jacketed during the hot isostatic pressing process to prevent fluid transmission between the blank and the furnace and ensure that the pressure can effectively act on the surface of the blank. The commonly used jacket material is stainless steel, but the sintering temperature of tungsten-based materials is as high as 1700°C, which is beyond the working temperature range of stainless steel. During the experimental research, niobium plates and tantalum plates were tried as jacket materials, but niobium is expensive and has a high cost, while tantalum is even more expensive.

[0095] Secondly, after hot isostatic pressing, the jacket needs to be removed. Since materials such as niobium and tantalum have similar properties to tungsten, they will fuse with the tungsten-based material after sintering and are difficult to separate. This results in the jacket being removed only by turning or cutting, which results in a very low actual material recovery rate and significantly increases production costs.

[0096] Third, hot isostatic pressing sintering is carried out in a closed package without impurity removal. This means that the gas elements and low-melting-point impurities in the tungsten powder will be enclosed in the sintered blank, resulting in the impurity content of the product being much higher than that of the medium-frequency sintered product. This increase in impurities will cause the product to become brittle and its strength to decrease. Therefore, even without considering the cost factor, hot isostatic pressing technology has serious defects in the quality of tungsten-based material products.

[0097] Therefore, the present invention seals the pores on the surface of the green compact by medium frequency sintering, and the subsequent hot isostatic pressing does not require a jacket.

[0098] Example 1

[0099] The preparation method of the high-density fine-grained doped tungsten-based material (W-0.5wt%ZrC) of this embodiment comprises the following steps:

[0100] S1. Add 600 mL of anhydrous ethanol and 8 kg of carbide balls to 3.98 kg of tungsten powder and 20 g of ZrC powder (D50 = 0.1 μm) in a ball mill, and wet grind at 60 rpm for 12 hours; then dry in a vacuum oven at 70 ° C for 16 hours, and sieve through a 120-mesh sieve twice to obtain doped tungsten powder.

[0101] S2. The doped tungsten powder is pressed into a green compact by cold isostatic pressing at a pressure of 200 MPa for 10 minutes. In addition to pressing into a green compact, a small test rod is also pressed by cold isostatic pressing. The small test rod is used for sampling during medium frequency sintering. This avoids damaging the integrity of the green compact by sampling and affecting subsequent processing.

[0102] S3. Medium frequency sintering: The compact is kept for 10 minutes during the medium frequency sintering process. 3 / h of hydrogen flow rate, and then raise the temperature to four insulation platforms for insulation, the four insulation platforms are respectively 900℃ for 2h, 1150℃ for 3h, 1450℃ for 3h, and 1700℃ for 2h;

[0103] When the temperature reaches 1800℃, turn off the hydrogen, then continue to heat up to 2030℃ and keep at this temperature for 1h. Finally, after the intermediate frequency sintering is completed, the furnace needs to be cooled to 20℃ before hot isostatic pressing.

[0104] Among them, the heating rate during the medium frequency sintering process is 10℃ / min;

[0105] The mass of the compact after medium frequency sintering is 3.56kg, and the material loss is 11%. Among them, the natural loss is not much, but because of multiple sampling, 150g of material of the small test bar is consumed;

[0106] Hot isostatic pressing: The temperature was raised to 1750°C at a heating rate of 10°C / min and kept at a pressure of 150 MPa for 3 h to obtain 3.56 g of high-density fine-grained doped tungsten-based material.

[0107] The measured density of the high-density fine-grained doped tungsten-based material in this embodiment is 19.08 g / cm 3 , Theoretical density is 19.24g / cm 3 (Calculated using ZrC), according to the calculation formula relative density = measured density / theoretical density, the relative density is 99.17%.

[0108] Figure 1 The metallographic and grain data diagram of this embodiment (scale is 10μm), according to Figure 1 The calculated average grain intercept of the high-density fine-grained tungsten-based material of the embodiment is 3.1 μm, and the grain density is 81103 / mm 2 , the grain grade is 13.4.

[0109] Figure 2 2 is a scanning electron microscope image of this embodiment.

[0110] Figure 3 This is the energy spectrum diagram of this embodiment, showing that in addition to the main component W, there is also Zr doping.

[0111] Example 2

[0112] This embodiment is a method for preparing a high-density fine-grained doped tungsten-based material (W-1.0wt%ZrC).

[0113] The difference between this embodiment and embodiment 1 is that:

[0114] In S1, the tungsten powder is 3.96 kg and the ZrC powder is 40 g.

[0115] In S3, among the four insulation platforms, the insulation time at 1150°C is adjusted to 4 hours, and the insulation time at 1450°C is adjusted to 4 hours, and the remaining steps and processes are the same as those in Example 1.

[0116] The measured density of the high-density fine-grained doped tungsten-based material in this embodiment is 19.01 g / cm 3 , Theoretical density is 19.17g / cm 3 , its relative density is 99.17%.

[0117] Figure 4The metallographic and grain data diagram of this embodiment (scale is 10μm), which shows that the average intercept of the grains of the high-density fine-grained doped tungsten-based material of this embodiment is 2.2μm, and the grain density is 168809 / mm 2 , the grain grade is 14.4.

[0118] Figure 5 2 is a scanning electron microscope image of this embodiment.

[0119] The energy spectrum of this embodiment is not much different from the test results of embodiment 1.

[0120] Example 3

[0121] This embodiment is a high-density fine-grained doped tungsten-based material (W-0.5wt% Nd 2 O 3 ) preparation method.

[0122] The difference between this embodiment and embodiment 1 is that:

[0123] Nd 2 O 3 (D50=0.1μm) powder replaces the ZrC powder in Example 1.

[0124] The measured density of the high-density fine-grained doped tungsten-based material in this embodiment is 19.10 g / cm 3 , Theoretical density is 19.24g / cm 3 , its relative density is 99.27%.

[0125] Figure 6 The metallographic and grain data diagram of this embodiment (scale is 10μm), which shows that the average intercept of the grains of the high-density fine-grained doped tungsten-based material of this embodiment is 2.6μm, and the grain density is 116383 / mm 2 , the grain grade is 13.9.

[0126] Figure 7 2 is a scanning electron microscope image of this embodiment.

[0127] Figure 8 This is the energy spectrum diagram of this embodiment, showing that in addition to the main component W, there is also Nd doping; it should be noted that, Figure 8 The peaks of O and Nd are higher, even higher than the main component W. This is because the X-rays hit Nd 2 O 3 The test conditions of the subsequent embodiments are similar and will not be explained one by one.

[0128] Example 4

[0129] This embodiment is a high-density fine-grained doped tungsten-based material (W-0.5wt%Sm2 O 3 ) preparation method.

[0130] The difference between this embodiment and embodiment 1 is that:

[0131] Sm 2 O 3 (D50=0.1μm) powder replaces the ZrC powder in Example 1.

[0132] The measured density of the high-density fine-grained doped tungsten-based material in this embodiment is 19.09 g / cm 3 , Theoretical density is 19.25g / cm 3 , its relative density is 99.17%.

[0133] Fig. 9 The metallographic and grain data diagram of this embodiment (scale is 10μm), which shows (the following grain data are obtained based on the metallographic diagram) that the average grain intercept of the high-density fine-grained tungsten-based material doped in this embodiment is 2.7μm, and the grain density is 105517 / mm 2 , the grain grade is 13.8.

[0134] Fig.10 2 is a scanning electron microscope image of this embodiment.

[0135] Fig.11 This is the energy spectrum diagram of this embodiment, showing that in addition to W as the main component, there is also Sm element doping.

[0136] Example 5

[0137] This embodiment is a high-density fine-grained doped tungsten-based material (W-0.5wt% CeO 2 ) preparation method.

[0138] The difference between this embodiment and embodiment 1 is that:

[0139] CeO 2 Powder (D50=0.1 μm) replaced the ZrC powder in Example 1.

[0140] The measured density of the high-density fine-grained doped tungsten-based material in this embodiment is 19.11 g / cm 3 , Theoretical density is 19.24g / cm 3 , its relative density is 99.32%.

[0141] Fig.12 The metallographic and grain data diagram of this embodiment (scale is 10μm), which shows that the average intercept of the grains of the high-density fine-grained doped tungsten-based material of this embodiment is 3.1μm and the grain density is 83069 / mm 2, the grain grade is 13.4.

[0142] Fig.13 2 is a scanning electron microscope image of this embodiment.

[0143] Fig.14 This is the energy spectrum diagram of this embodiment, showing that in addition to W as the main component, Ce element is also doped.

[0144] Example 6

[0145] This embodiment is a high-density fine-grained doped tungsten-based material (W-0.5wt% Y 2 O 3 ) preparation method.

[0146] The difference between this embodiment and embodiment 1 is that:

[0147] Y 2 O 3 Powder (D50=0.1 μm) replaced the ZrC powder in Example 1.

[0148] The measured density of the high-density fine-grained doped tungsten-based material in this embodiment is 19.07 g / cm 3 , Theoretical density is 19.23g / cm 3 , its relative density is 99.17%.

[0149] Fig.15 The metallographic and grain data diagram of this embodiment (scale is 10μm), which shows that the average intercept of the grains of the high-density fine-grained doped tungsten-based material of this embodiment is 2.9μm, and the grain density is 95425 / mm 2 , the grain grade is 13.6.

[0150] Fig.16 2 is a scanning electron microscope image of this embodiment.

[0151] Fig.17 This is the energy spectrum diagram of this embodiment, showing that in addition to the main component W, there is also doping of Y element.

[0152] Comparative Example 1

[0153] The difference between this comparative example and Example 1 is:

[0154] The heating process of this comparative example includes two heat preservation platforms: the temperature of the first heat preservation platform is 180°C, and it is kept at this temperature for 2 hours; the temperature of the second heat preservation platform is 1600°C, and it is kept at this temperature for 3 hours;

[0155] Then, the high-temperature sintering temperature is set to 2300° C. and kept at 2300° C. for 18 hours; the other steps and processes are the same as those in Example 1.

[0156] The measured density of the tungsten-based material doped in this comparative example is 18.76 g / cm 3 , the theoretical density is 19.24g / cm 3 , its relative density is 97.51%.

[0157] Fig.18 The metallographic and grain data diagram of the doped tungsten-based material of this comparative example shows that the average intercept of the doped tungsten-based material of this comparative example is 267 μm and the grain density is 11 / mm 2 The grain size of the doped tungsten-based material sintered by the medium frequency sintering process in this comparative example is two orders of magnitude larger than that of Example 1; the primary reason why the doped tungsten-based material in Comparative Example 1 is coarser is the difference in temperature and time of medium frequency sintering.

[0158] In addition, it should be noted that the particle size of the raw material powder is one of the important factors controlling the grain size and density. The present invention uses 06 type tungsten powder, which has a finer particle size and higher activity. Under the condition of keeping the particle size as a single variable, the sintering process must be strictly controlled to prevent excessive grain growth.

[0159] Fig.19 This is the cross-sectional electron microscope image of the product after medium frequency sintering in this comparative example. Because the grains are too coarse, no obvious grains can be seen in the image.

[0160] Comparative Example 2

[0161] The difference between this comparative example and Example 1 is:

[0162] The temperature of hot isostatic pressing is raised to 2100°C.

[0163] The measured density of the doped tungsten-based material in this comparative example is 19.12 g / cm 3 , the theoretical density is 19.24g / cm 3 , its relative density is 99.38%.

[0164] Fig. 20 The metallographic and grain data diagram of this comparative example (scale is 100μm), showing that the average intercept of the grains of the doped tungsten-based material of this comparative example is 751μm and the grain density is 1.4 / mm 2 , the grain grade is -2.5.

[0165] Fig.21 This is a cross-sectional electron microscope image of the doped tungsten-based material of this comparative example. The grains are coarser than those in comparative example 1, and the grains are even less visible in the image.

[0166] It can be seen that the doped tungsten-based material prepared in Comparative Example 2 is coarser than that in Example 1. From the perspective of grain size, the difference between the two is huge, which shows that this temperature process is completely unsuitable for making fine-grained tungsten-based products.

[0167] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The specific embodiments described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-density fine-grained doped tungsten-based material, characterized in that: The following steps are involved: S1. Wet-grinding and drying the tungsten powder and the metal compound powder to obtain a doped tungsten powder; The metal compound is an oxide of a IIIB~VB group element or a carbide of a IIIB~VB group element; The carbide of the IIIB~VB group element is one of ZrC, HfC and TiC; The oxide of the IIIB~VB group element is one of La2O3, CeO2, Sm2O3, Y2O3 and Nd2O3; S2. The tungsten-doped powder is pressed into a compact to obtain a green compact; S3. The compact is subjected to medium frequency sintering and hot isostatic pressing to obtain a high-density fine-grained doped tungsten-based material; The medium frequency sintering is divided into a heating process and a high temperature sintering process; The heating process includes four insulation platforms: the temperature of the first insulation platform is 800-1000°C, the temperature of the second insulation platform is 1050-1250°C, the temperature of the third insulation platform is 1350-1550°C, and the temperature of the fourth insulation platform is 1600-1800°C; the set temperature of the high temperature sintering is 1900-2100°C; The set temperature of the hot isostatic pressing is 1650~1850℃.

2. The method for preparing a high-density fine-grained doped tungsten-based material according to claim 1, characterized in that: The particle size of the tungsten powder is 0.5-1.0 μm; The purity of the tungsten powder is ≥99.9%; The particle size of the metal compound powder is 0.01-1.0 μm; The content of the metal compound in the doped tungsten powder material is 0.5-2.0 wt %.

3. The method for preparing a high-density fine-grained doped tungsten-based material according to claim 1, characterized in that: The drying temperature is 50-90°C; The drying time is 12 to 24 hours; After the drying, the mixture needs to be sieved through a 120-mesh sieve twice.

4. The method for preparing a high-density fine-grained doped tungsten-based material according to claim 1, characterized in that: The pressing method is cold isostatic pressing; The pressing pressure is 160-240 MPa; The holding time of the pressing is 5 to 10 minutes.

5. The method for preparing a high-density fine-grained doped tungsten-based material according to claim 1, characterized in that: The heating process includes four insulation platforms, and the insulation time at each insulation platform is independently selected from 1 to 4 hours; The heating rate of the medium frequency sintering is 2-30°C / min; The heating process needs to keep hydrogen flowing, and the hydrogen flow rate is 5~20 m 3 / h; After reaching the set temperature of the high temperature sintering, keep the temperature for 0.5 to 2 hours; When the medium frequency sintering temperature reaches 1800-2000°C, the introduction of hydrogen is stopped.

6. The method for preparing a high-density fine-grained doped tungsten-based material according to claim 1, characterized in that: After the medium frequency sintering, the furnace needs to be cooled to 20-25°C.

7. The method for preparing a high-density fine-grained doped tungsten-based material according to claim 1, characterized in that: The hot isostatic pressing pressure is 100-200 MPa; The set temperature of the hot isostatic pressing is 1700-1800°C; After the hot isostatic pressing is heated to the set temperature, it is kept at this temperature for 2.0 to 4.0 hours.

8. A high-density fine-grained doped tungsten-based material prepared by the method for preparing a high-density fine-grained doped tungsten-based material as claimed in any one of claims 1 to 7.

9. The high-density fine-grained doped tungsten-based material according to claim 8, characterized in that: The measured density of the high-density fine-grained tungsten-based material is 19.0-19.2 g / cm 3 ; The relative density of the high-density fine-grained doped tungsten-based material is ≥99%; The grain density of the high-density fine-grained tungsten-based material is 60,000 to 200,000 grains / mm 2 ; The average grain intercept of the high-density fine-grain doped tungsten-based material is 2-4 μm.

Citation Information

Patent Citations

  • Preparation method of high-density rare earth tungsten electrode

    CN110788318A

  • Preparation method of high-density fine-grain tungsten-based material

    CN109457159A

  • A method for preparing high-strength and high-ductility dispersion-strengthened tungsten alloys

    CN114934207A

  • Preparation method of fine-grain oxide doped tungsten-based material

    CN117778793A